Inscription on a pillar in the Mahamandapa - Temples of India Project Team (Jio Institute, 2024)
This inscription, dated 1187 CE (VS 1244), was composed during the reign of Prithivaraja Chauhan and records the donation of two sword handles to the mandapa (pillared hall) of the temple of Sri Gokarna in Vigrahapura (Bisalpur). It is inscribed on a pillar in the mahamandapa (pillared hall) alongside other informative inscriptions. The inscription underscores the strong association between the city of Vigrahapura (Bisalpur) and King Vigraharaja IV, also known as Bisaldeo, who is celebrated in oral accounts and medieval bardic accounts as the temple’s patron. The mention of the city’s name in the solidifies this connection. Furthermore, it establishes the original name of the temple as the temple of Gokarna, derived from the name of the shivalinga housed within a nearby cave in the village.